Endovascular Treatment (Stenting) of Total IVC Obstruction with Collaterals in Young Adult with Crohn’s Disease Maharishi Markandeshwar (Deemed to Be University) (Indian Journal of Public Health Research & Development, 2020)
We present a case of clinically extensive bilateral DVTs associated with chronic total inferior vena cavathrombosis with underlying crohn’s disease and who is on steroid therapy. Young patients presenting withsymptoms of DVT should be investigated not only to establish any thrombophilic pre-disposition but toascertain the proximal extent of thrombus which may itself influence treatment. Treatment options in thecase of IVC thrombus without anatomical variance include anticoagulation, mechanical thrombectomy,systemic thrombolytic therapy, transcatheter regional thrombolysis, and angioplasty
Keywords: Deep vein thrombosis, inferior vena cava thrombus, IVC stenting, Chronic total IVC occlusion, chron’s disease